ANALISIS KELAYAKAN USAHATANI SEMANGKA DI DESA TUNGKU JAYA KECAMATAN SOSOH BUAY RAYAP KABUPATEN OKU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2019)
The Analysis of Feasibility of Watermelon Farming in Tungku Jaya Village, Sub district of Sosoh Buay Rayap, Ogan Komering Ulu Regency. This study aims to analyze the income and feasibility of water melon farming in Tungku Jaya Village, Sub district of Sosoh Buay Rayap, Ogan Komering Ulu Regency. This research was conducted in Tungku Jaya Village, Sub district of Sosoh Buay Rayap, Ogan Komering Ulu Regency. The method used in this research is survey method. Data were obtained by interview and face-to-face interview with respondent using questionnaire as data collecting tool. The sampling method used is the case study method. The population in this research is watermelon farming farmers with a total of 13 farmers. The results of research conducted, it can be concluded that the production income generated by watermelon farmers is Rp. 38.247.482 Ha/MT and the feasibility of watermelon farming in Tungku Jaya Village, Sub district of Sosoh Buay Rayap, Ogan Komering Ulu Regency is 2,074.